Respecting Elders and Community Norms: Understanding the Adat Prohibition on 'Nikah Malem Songo Geblake Mbah - Rinwanto Rinwanto; Nurul Hakim; Farida Isroani; Yudi Arianto (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to explore the prohibition of